ANALISIS YURIDIS PERAN HAKIM MEDIATOR DALAM MEDIASI PERCERAIAN UNTUK MEWUJUDKAN KEPASTIAN HUKUM (STUDI PENELITIAN DI PENGADILAN AGAMA KELAS 1-A BATAM) - Febri Yansah Putra; Laily Waslihati; Christiani Prasetiasari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The involvement of mediators in divorce disputes is only a trigger for the parties to reach a peaceful settlement, so that in general the mediator does not interfere in determining the contents of the peace agreement. The mediator is in a middle and neutral position between the disputing parties, and tries to find a number of agreements so that it becomes a satisfactory outcome for the litigants. The role of Religious Court Judges in the trial process is first and foremost, the aim is to reconcile the litigants, because reconciling is the main priority. The research in this thesis uses the type of normative research (legal research), which uses legal sources in the form of laws and regulations, court decisions/decisions, contracts/agreements/contracts, legal theory, and the opinions of scholars. Which is supported by empirical research, namely the approach carried out by means of research observations in the field. The Batam Class 1-A Religious Court has carried out the mandate of the Supreme Court in resolving divorce cases through mediation in accordance with Supreme Court Regulation Number 1 of 2016. Divorce cases registered at Batam's Class 1-A Religious Courts which are resolved through mediation have very low success rates. One of the obstacles in conducting mediation is that the parties have agreed to divorce and the lack of public knowledge about the importance of mediation.Keywords: The Role of Judges, Divorce, Mediation.